Nuclear magnetic resonance spectroscopy: A comprehensive tool for analyzing liquid products in electrochemical CO2 reduction - Aymen S. Abu Hatab (18811339) (2025)
The electrochemical reduction of carbon dioxide (eCO2RR) has become a very promising pathway that can be used in the transformation of CO2 to important chemical products and, thus, is one of the mitigations of climate change and will contribute toward sustainable chemical production. This review aims at presenting the importance of Nuclear Magnetic Resonance spectroscopy (NMR) to analyze and quantify the liquid-phase products obtained by eCO2RR. This provides a summary regarding the role that NMR plays in the process of reducing carbon dioxide. The following discusses the benefits: identification, complete elucidation, and follow-up on reactions involving CO2 electro-reduction. Pulse experiments corresponding to different methods for water signal suppression are considered separately, outlining some recent developments in the interference water signal reduction which is very crucial for the correct NMR data acquisition in aqueous electrolytes. Certain selected products are described, like carbon monoxide (CO)-associated liquids, formic acid, methanol, and formaldehyde as examples of the NMR precision for the characterization of important compounds. Further, the quantification of C2 products such as ethanol and acetate is discussed in order to illustrate how the technique can be applied in the elucidation of reaction mechanisms and optimization of catalyst performance. This review covers challenges, advanced methodologies, and emerging trends in order to underline the transformative role that NMR plays in advancing CO2 electrochemical reduction toward sustainable chemical synthesis. Other Information Published in: Journal of Electroanalytical Chemistry License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jelechem.2025.119097